Analisis VAR (Vector Autograsive) Permintaan Dan Penawaran Kunjungan Wisatawan Domestik Di Kabupaten Lombok Utara (KLU) - Sutanto, Himawan (Jurnal Ekonomi dan Bisnis, 2018)
This research is entitled "Analysis of VAR (Vector Autograsive) Requests and Offers of Tourist Visits in North Lombok Regency (KLU)". The formulation of the problem in this study are (a) whether the variables that determine the demand and supply of tourists in North Lombok Regency (KLU), (b) are the variables that determine the demand and supply of tourists in North Lombok Regency (KLU)? (a) to find out the variables that determine the demand and supply of tourist visits in North Lombok Regency (KLU), (b) to find out the variables that most determine the demand and supply of tourist visits in North Lombok Regency (KLU. Data used in this study Secondary data from KLU Tourism Office, NTB Central Bureau of Statistics (BPS), Bank Indonesia The research variables used were tourist visit requests and offers in North Lombok Regency (KLU) such as NTB Inflation Rate, NTB GRDP, KLU Inflation, GRDP KLU The data analysis technique used in this research is VAR Analysis (Vector Autograsive) with b ante software Eviews. The results of the study showed that the Province Inflation Variables, Provincial GRDP had a significant effect on Domestic Tourist requests in North Lombok Regency (KLU).